Analisis Kesesuaian Lahan dan Daya Tampung untuk Perumahan di Kawasan Rawan Banjir dan Longsor di Desa Sidorejo, Kecamatan Godean serta Arahan Pengelolaannya - Fardede, Asha Uswatun Hasanah; Khasanah, Hetty Nurjamiatun; Nababan, Putri Pintauli; Rafianto, Rio Azurizqi (Prosiding Seminar Nasional Mini Riset Mahasiswa, 2025)
Rapid population growth in urban areas has driven an increase in the need for land for various activities, especially settlements. This study aims to analyze the suitability of land and environmental carrying capacity for settlement development in Bukit Pandawa, Sidorejo Village, Godean District, Sleman Regency. The methods used include spatial analysis and field surveys by considering several physical parameters of the land, namely slope, soil depth, texture, gravel content, drainage, and flood potential. One striking example occurs in Bukit Pandawa, Sidorejo Village, Godean District, Sleman, where the hilly area which is part of the Gunung So Ridge is engineered to support housing development. In fact, the area has a pyroclastic rock lithology that has undergone advanced weathering, plus a steep slope, so it has a high potential for landslide hazards. The unsuitability of land for use as a settlement without proper slope management can endanger the safety and sustainability of development. Therefore, analysis of land suitability and carrying capacity is important in spatial planning, in order to ensure safe, sustainable land use, and in accordance with the physical characteristics of the area.